2017
DOI: 10.1158/1940-6207.capr-17-0174
|View full text |Cite
|
Sign up to set email alerts
|

Caloric Restriction Prevents Carcinogen-Initiated Liver Tumorigenesis in Mice

Abstract: Caloric restriction (CR) and endurance exercise elicit wide-ranging health benefits including reduced risk of select cancers. In addition, diet composition influences oncogenesis, although its interactions with exercise and CR are not well understood. Therefore, to investigate the potential interactions between diet and lifestyle interventions on liver tumorigenesis, the carcinogen diethylnitrosamine was administered to 72 male C57Bl/6 mice that were subsequently fed diets enriched with lard (CTL) or olive oil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…In a colon cancer model EPA also reduced MMP9 cytokine production via NOTCH1 signaling to exhibit protective effects ( Fazio et al, 2016 ). Alternatively, caloric restriction has been suggested as a mechanism to alter metabolic pathways in NDEA-induced HCC rather than diet leading to altered inflammation, oxidative stress, cell migration, injury and oncogenesis ( Ploeger, Manivel, Boatner, & Mashek, 2017 ). Human plasma and serum found to consist of eicosanoids and SPMs, additional omega-3 or acetylsalicylic acid supplementation also increased plasma SPM levels inducing increased phagocytosis ( Colas, Shinohara, Dalli, Chiang, & Serhan, 2014 ).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…In a colon cancer model EPA also reduced MMP9 cytokine production via NOTCH1 signaling to exhibit protective effects ( Fazio et al, 2016 ). Alternatively, caloric restriction has been suggested as a mechanism to alter metabolic pathways in NDEA-induced HCC rather than diet leading to altered inflammation, oxidative stress, cell migration, injury and oncogenesis ( Ploeger, Manivel, Boatner, & Mashek, 2017 ). Human plasma and serum found to consist of eicosanoids and SPMs, additional omega-3 or acetylsalicylic acid supplementation also increased plasma SPM levels inducing increased phagocytosis ( Colas, Shinohara, Dalli, Chiang, & Serhan, 2014 ).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Continued studies have shown that as a form of hypurgia, fasting prevents tamoxifen‐induced endometrial hyperplasia and improves the effect of estrogen therapy on hormone receptor‐positive breast cancer 41 . Similarly, CR reduces the incidence of intestinal polyps, 15 liver oncogenesis, 42 and skin tumorigenesis 43 and serves as a potential therapeutic option for colorectal cancer 44 . Fasting also reduces chemotherapy toxicity and prolongs survival time in a mouse model of neuroblastoma 45 .…”
Section: Discussionmentioning
confidence: 99%
“…TE also reduced body weight gains caused by HFD, possibly related to green tea’s effects on thermogenesis and fat oxidation (42). In this context, a recent study reported that caloric restriction diet inhibits DEN-induced liver tumorigenesis in mice which may involve multifaceted mechanisms (43). The antioxidant effects of catechins may be due in part to increased activities of catalase, superoxide dismutase and glutathione peroxidase (44).…”
Section: Discussionmentioning
confidence: 99%